2015
DOI: 10.1111/apt.13376
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: microbial dysbiosis and nonalcoholic fatty liver disease

Abstract: Summary Background The human intestinal microbiota is a key regulator of host metabolic and immune functions and alterations in the microbiome (‘dysbiosis’) have been implicated in several human diseases. Because of the anatomical links between the intestines and the liver, dysbiosis may also disrupt hepatic function and thereby contribute to the pathogenesis of nonalcoholic fatty liver disease (NAFLD). Aim To perform a comprehensive review of the medical literature investigating associations between intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(165 citation statements)
references
References 80 publications
4
143
0
6
Order By: Relevance
“…The human gut microbiota contains more than 100 fold genes than its host [16] and has been suggested to be an important environmental factor involved in the pathogenesis of NAFLD [17,18]. There is an anatomical link between the intestine and liver via the hepatic portal system.…”
Section: Introductionmentioning
confidence: 99%
“…The human gut microbiota contains more than 100 fold genes than its host [16] and has been suggested to be an important environmental factor involved in the pathogenesis of NAFLD [17,18]. There is an anatomical link between the intestine and liver via the hepatic portal system.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the observed increased levels of blood-ethanol in NASH patients are a consequence of endogenous production by gut microbiota is still a subject of debate [98,99]. A recent systematic review addressing the association of dysbiotic microbiota composition with NAFLD concluded an association but no evidence for causality [100]. However, recent animal models demonstrate how the innate immunity (toll-like and NOD-like receptors) of gut epithelium critically regulates the gut microbiota, thereby controlling the progression of NAFLD and NASH.…”
Section: Antibiotics - Friend or Foe In The Pathogenesis And Course Omentioning
confidence: 99%
“…2). Emerging evidence suggests that the severity of NAFLD postnatally is strongly associated with gut dysbiosis 99 and a shift in gut metabolic function, including production and utilization of shortchain fatty acids (SCFAs) and bile acids 100103 . The functions of SCFAs and bile acids in NAFLD have been reviewed elsewhere 104 .…”
Section: Early Postnatal Factorsmentioning
confidence: 99%